The world of the counselor an introduction to the counseling profession - Neukrug, Ed (Brooks/Cole Publishing Company, 1998)
Using a personal tone, the author writes a thorough text for counsellor-educators that combines the general topics of what counsellors do and the skills that counsellors use.